EVALUASI STRATEGI BERSAING PADA PERUSAHAAN Studi Kasus pada PT Draff Cipta Artha - , Dollyansyah Taufika, Prof. Dr. Djoko Susanto, MSA. Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Company is an organisation that seeks for benefit within its environment. Gaining benefit such as maximum revenue is one of company main goal. Along with industrial development in goods and services, company strategy is demanded to be appropriate in order to fit market condition. Company top leaders are required to have abundant and sufficient skill to reach and achieve company vision and mission. As a decision maker, top company leader have a huge influence to decide the direction of company is heading. The main purpose of this research is to evaluate applied company strategy and analyse factors that contribute in a process of strategic decision making. Data being collected in this research is gathered from respondent and secondary data is gained from company documentations and reports. There are 4 respondent is this research, they are directors of the company who have role in stating and deciding company strategy. The mechanism used to evaluate factors that influence strategic decision making are by analysing internal and external factors which the result of it is placed into SWOT matrix to help company to understand more of a better available options they are facing. Using tools such as QSPM, company is able to sort their strategy options base on priority scale.